Chronic Wounds: A Nursing Approach to Effective Care - Ashwaq Mohammed Alshahrane, Malak Mohammed Aljohani, Tahani Hassan Abuillah, Farjah Ali Abishi, Majed MahliMutairan Alharbi, Sharifh Mohmmad Alasmari, Elham Mohammed Thubab, Fahad Nayidh Alotaibi; Noor Saeed Alotaibi, Shaia Sheliwih Alotibi, Taghreed Rumah Alotaibi, Issa Rabah Alrashidi, Fatimah Hussien Ibrahiem Alnakhli, Sarah Abdullah Alhayfani, Maalem Dhawi Alnafiai (Journal of International Crisis and Risk Communication Research, 2024)
Chronic wounds, which fail to heal within the expected timeframe, pose significant challenges to patients and healthcare systems worldwide. These wounds are classified into pressure ulcers, diabetic foot ulcers, venous leg ulcers, and arterial insufficiency ulcers, each requiring specialized treatment. Nurses play an indispensable role in chronic wound care, combining their knowledge of advanced wound care technologies, patient education, and multidisciplinary collaboration to improve outcomes. This paper explores the physiological aspects of wound healing, discusses the challenges in managing various types of chronic wounds, and highlights the importance of evidence-based nursing practices. Innovative approaches, such as nanotechnology and biologic therapies, offer promising advancements in chronic wound care, reinforcing the nurse's role in implementing these therapies. The findings underscore the critical need for continuous education and professional development for nurses in this evolving field.